2009
DOI: 10.1016/j.optcom.2009.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Improved design of a DFB Raman fibre laser

Abstract: Abstract:A Raman fibre laser based on phase shifted DFB structures is modelled for the first time.Using parameters of realistic devices, the model predicts low-threshold and highly-efficient laser output. The change of position and width of the phase shift were found to have a substantial impact on laser performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…As mentioned previously the R-DFB signal acts as the pump for FWM. It possesses a nonuniform intensity distribution within the DFB cavity [22][23][24], as seen in Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously the R-DFB signal acts as the pump for FWM. It possesses a nonuniform intensity distribution within the DFB cavity [22][23][24], as seen in Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the amplitudes of the forward, ) ( 1 z A f , and backward, ) ( 1 z A b , R-DFB signals along the DFB grating length of L are given by Eqs. (1) and (2) [23], where κ is the coupling coefficient of the DFB grating. Thirdly, single-mode fiber is utilized and all the overlap integrals of the waves are assumed to be identical to…”
Section: Discussionmentioning
confidence: 99%
“…This would therefore open up the prospect of generating high-power narrow linewidth low-noise oscillation at any desired wavelength ranging from the visible to the infrared region, pending only the availability of a suitable pump source [5][6]. Theoretical studies suggest that Raman DFB fibre lasers could be made comparatively efficient by employing π phase-shifted fibre Bragg gratings of only a few tens of centimetres of passive germanium doped silica fibres, and also that these should exhibit only watt-level threshold [7][8]. Only recently an experimental demonstration of Raman DFB fibre laser operating at 1.58µm was reported [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was also predicted that mode competition within the grating structure could cause instability of the laser oscillation. In order to reduce the lasing threshold as well as mode competition, R-DFB fiber lasers based in π phase-shifted DFB gratings were studied numerically by Hu and Broderick, and Shi and Ibsen who showed that watt-level threshold R-DFB fiber lasers would be possible from much shorter length π phase-shifted DFB gratings of only several 10 s of centimeters in length [8,9].…”
mentioning
confidence: 99%